Revealing Media Neutrality : (Case Study of Reporting on The Revocation of Bharada Richard Eliezer’s Protection by LPSK) - Basri, Solluuhiyyah; Zahro', Nida Hamidatuz; Al-harithy, Sierra Larose; Jannah. S, Putri Inayatul; Salsabiilla, Wafiq (Commsphere: Jurnal Ilmu Komunikasi, 2023)
Independence and neutrality are ideologies that must be applied in a news story. The media has rights and obligations to ensure these two ideologies match events. The media has also experienced convergence from several types of print news to transforming into digital media online. Reporting current issues, which is the media's function, is exciting to discuss. Here, the researcher analyzes the case of Richard Eliezer's revocation of protection by the LPSK, which was very hotly discussed by the public last March. This study uses qualitative methods and analysis (DNA) with application support dna-2.0-beta25, visone-2.15, and JavaSetup8u321. Researchers found that six media portals analyzed in the reporting of Richard Eliezer's revocation of protection by LPSK, namely Kompas TV, TV One, Metro TV, CNN, Republika, and Tribune, have different alignments. Three of the six media above tend to be neutral; two other portals are pro, and one is contra. In this way, each media has its alignment according to the interests of related parties, which have a background unknown to the public. Keywords: Neutrality, Media, Revoking, Bharada E’s Protection